Impact of Malnutrition and Smoking Habits of Parents on ARI - Bari, MI; Haque, MI; Siddiqui, AB; Haidary, MH; Hossain, MA (TAJ: Journal of Teachers Association, 2011)
Acute Respiratory Infection (ARI) is one of the leading common causes of death in young children in Bangladesh. Three hundred fifty one patients of ARI below five years of age are selected as per WHO guidelines. Out of 351 patients, one patient died due to very severe pneumonia with severe malnutrition. There was male preponderance in all the age groups and also 41% of male children had recurrent attacks of ARI. In this study, it was statistically proved that malnutrition (p=Q.00028) and smoking habits of parents (p=0.04054) had significant important risk factors on recurrent attacks of ARI. DOI: http://dx.doi.org/10.3329/taj.v14i2.8390 TAJ 2001; 14(2): 74-77